2017
DOI: 10.1099/jmm.0.000392
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium acnes is developing gradual increase in resistance to oral tetracyclines

Abstract: Propionibacterium acnes is an anaerobic bacterium that causes deep infection in organs and prosthetic joints, in addition to acne vulgaris. Many tetracycline-resistant P. acnes strains have been isolated because oral tetracyclines are frequently used as an acne treatment against P. acnes. In this study, we found a novel tetracycline resistance mechanism in P. acnes. Three doxycycline-resistant (MIC: 16 µg ml-1) strains were isolated from 69 strains in acne patients in Japan between 2010 and 2011. Additionally,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Therefore, we need to analyze the complete sequence of pTZC1 in the other C. acnes isolates because pTZC1 has a possibility to differ in C. acnes strains. Until now, the decreased susceptibility of C. acnes to tetracyclines was caused by the acquisition of mutations in 16S rRNA and the S10 ribosomal protein, whereas an extrachromosomal resistance determinant has not been reported in C. acnes (17,18). Our findings strongly suggest that dissemination of the strains carrying pTZC1 will cause increased prevalence of C. acnes strains with decreased susceptibility to tetracyclines in the future.…”
Section: Discussionmentioning
confidence: 65%
“…Therefore, we need to analyze the complete sequence of pTZC1 in the other C. acnes isolates because pTZC1 has a possibility to differ in C. acnes strains. Until now, the decreased susceptibility of C. acnes to tetracyclines was caused by the acquisition of mutations in 16S rRNA and the S10 ribosomal protein, whereas an extrachromosomal resistance determinant has not been reported in C. acnes (17,18). Our findings strongly suggest that dissemination of the strains carrying pTZC1 will cause increased prevalence of C. acnes strains with decreased susceptibility to tetracyclines in the future.…”
Section: Discussionmentioning
confidence: 65%
“…Tetracycline resistance is associated with chromosomal point mutation in the 16s rRNA gene of C. acnes [69]. C. acnes becomes less susceptible to doxycycline when amino acid is substituted in the ribosomal S10 protein [131].…”
Section: Acne Treatment and Skin Microbesmentioning
confidence: 99%
“…Unfortunately, resistance to these antibiotics is beginning to emerge. 56 However, recent work has demonstrated that natural products from Staphylococcus epidermidis , such as succinic acid, can effectively inhibit the growth of P. acnes . 56 Gaining a better understanding of the molecular mechanism by which products like succinic acid inhibit P. acnes growth may provide the basis of naturally based small molecules that more effectively target this organism and prevent infection from occurring.…”
Section: Precision Treatment For Skin Infectionsmentioning
confidence: 99%